Paleocene-Eocene foraminifera from the Tuz Gölü Basin (Salt Lake Basin, Central Türkiye) and their paleoenvironmental interpretations - Aynur Hakyemez; Alper Bozkurt; Mustafa Yıldız; Muhittin Görmüş (Bulletin of the Mineral Research and Exploration, 2024)
Paleocene-Eocene aged sediments from the east of Tuz Gölü Basin (Central Türkiye) provide significant data for foraminifera contents and their paleoenvironmental clues. They are important in revealing the stratigraphy of the region and the Paleocene-Eocene geological history of Türkiye. The sediments, composed mainly of carbonates, are known as Karapınaryaylası Formation. In this formation, benthic foraminifera representing SBZ2 to SBZ12 biozones corresponding to the Selandian-Late Cuisian time interval were identified in ten measured stratigraphical sections. The zonal interval from the E7 Zone (late Ypresian) to the E10 Zone (Lutetian) is characterized by the marker species of planktonic foraminifera defined in the clayey limestones from the uppermost part. The studied formation is divided into four main facies and eleven sub-microfacies types. The clayey limestone levels of the Karapınaryaylası Formation, which generally starts with a transgressive sequence, contain abundant planktonic foraminifers, while the lithologies of grainstone, packstone and wackestone are rich in benthic foraminifers. Benthic foraminifer assemblages indicate different paleoenvironments from lagoon to back-bank, bank and fore-bank. The obtained foraminiferal data show the Selandian-Lutetian age range and various paleoenvironments from the lagoon to the open sea.